Chronic pain and associated factors in Maputo, Mozambique: a pilot study - Walters, Camila B (Br J Pain, 2018)
INTRODUCTION: Studies estimate that 20% of adults suffer from chronic pain. A meta-analysis in low- and middle-income countries (LMICs) found 34% had chronic pain. There are few studies on pain prevalence gathered in Africa. This study surveyed the capital city of Mozambique. METHODS: This was a cross-sectional study employed in a community setting. The Vanderbilt Global Pain Survey comprised questions on the behaviour and attitudes of respondents regarding pain, including previously validated metrics: the Pain Catastrophizing Scale, the World Health Organization Disability Assessment Schedule, the Brief Pain Inventory, Widespread Pain Index and Symptom Severity Score, and the Michigan Body Map. RESULTS: Ninety-seven surveys were completed out of 100. Pain every day lasting for more than 6 months in their lifetime was reported as 39.2% (CI: 29.4–49.6), and 52% of respondents had pain the day of the interview. However, the pain resulted in little difficulty with activities of daily living and maintaining relationships (61%–89%). Although none reported mental health disorders, 53.6% had experienced a traumatic event in their life, with 45.2% having related nightmares, anxiety, or fear. Most respondents (99%) would take oral medication if it helped their pain, with a large proportion willing to spend significant money for these (49% would pay >US$40) and willing to travel long distances to get help (55.2% would travel >40 kilometer). CONCLUSION: The prevalence of chronic pain in Maputo, Mozambique is similar to the average for LMICs. Trends in high-income countries suggest that multimodal pain management and multidisciplinary treatments may improve optimal pain control in LMICs.